Methylenetetrahydrofolate reductase (MTHFR) gene C677T (rs1801133) polymorphism and risk of alcohol dependence: a meta-analysis - Rai, Vandana (AIMS Neurosci, 2021)
Alcohol dependence is a complex neuropsychiatric disorder. Numerous studies investigated association between MTHFR gene C677T (rs1801133) polymorphism and alcohol dependence (AD), but the results of this association remain conflicting. Accordingly, authors conducted a meta-analysis to further investigate such an association. PubMed, Elsevier Science Direct and Springer Link databases were searched for studies on the association between the MTHFRC677T polymorphism and AD. Pooled odds ratio (OR) with 95% confidence interval (CI) was calculated using the fixed- or random-effects model. Statistical analysis was performed with the software program MetaAnayst and MIX.A total of 11 articles were identified through a search of electronic databases, up to February 28, 2020. The results of the present meta-analysis did not show any association between MTHFR C677T polymorphisms and AD risk (for T vs. C: OR = 1.04, 95% CI = 0.88–1.24; CT vs. CC: OR = 1.02, 95% CI = 0.62–1.68; for TT+CT vs. CC: OR = 1.10, 95% CI = 0.94–1.29; for TT vs. CC: OR = 1.01, 95% CI = 0.66–1.51; for TT vs. CT+CC: OR = 0.97, 95% CI = 0.66–1.40). Results of subgroup analysis showed no significant association between MTHFR C677T polymorphism with AD in Asian as well as in Caucasian population. In conclusion, C677T polymorphism is not a risk factor for alcohol dependence.